Long-term outcomes of the Universal 2 total wrist replacement: revision and loosening at 10 years and beyond. (July 2023) - Newton, Ashley; Kandemir, Göksu; Joyce, Thomas; Murali, Raj; Hayton, Michael; Talwalkar, Sumedh; Trail, Ian
The aim of this study was to ascertain the long-term revision rates of the Universal 2 wrist prosthesis in a previously published cohort of patients with rheumatoid arthritis. The time to, and reasons for revision were determined. Radiographs were analysed to determine whether loosening had occurred in the long-term according to the Wrightington zonal classification of loosening. Seventy-eight wrists from the original cohort of 85 wrists could be identified for analysis. The longest follow-up was 16 years and 29 wrists had follow-up beyond 10 years. Seventeen wrists had been revised or were on the waiting list for revision, an overall revision rate of 22%. The 10-year survivorship was 78%. Long-term revision was commonly for periprosthetic loosening with pain and component subsidence. In those with more than 10-year follow-up, significant lucency was seen in 16 carpal components and 15 radial components. Explant analysis showed significant polyethylene wear and we postulate this is the principal reason for component loosening. Level of evidence: IV